The implementation and evaluation of a nutrition education programme about Mediterranean diet for adolescents - Akar Sahingoz, Semra; Dogan, Leyla (Progress in Nutrition, 2019)
The purpose of this study is to assess the compliance of the dietary habits in adolescents with the Mediterranean diet by detecting their nutrition knowledge levels and to educate the adolescents on the Mediterranean diet. The research was conducted with adolescents aged between 11 and 16 years in Eskişehir Province. The experimental group (n=76) and the control group (n=84) were applied pretest and posttest. The experimental group was educated on the Mediterranean diet by using different teaching methods for a total of 18 hours (8 weeks). The compliance of the nutrition status of adolescents with the Mediterranean diet was assessed using the Mediterranean Diet Quality Index (KIDMED). Before the education, the KIDMED scores of 25.0% of adolescents had been poor (≤3 points), 56.6% of them had been medium (4-7 points) and 18.4% of them had been high (≥8 points) whereas after the education, the KIDMED score of all the adolescents (100 %) were high (≥8 points). In consequence of the education provided to the experimental group, the nutrition knowledge and KIDMED scores of the adolescents increased. It is important to provide individuals with proper nutrition knowledge and habits beginning from their childhood to prevent health problems at later ages.